1992
DOI: 10.1111/j.1365-2125.1992.tb05638.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the anticholinergic effect of the new antihistamine mizolastine in healthy subjects.

Abstract: 1. Twelve healthy subjects were enrolled in a double‐blind placebo controlled cross‐over study in order to assess the possible anticholinergic effects of four doses of a new antihistamine compound, mizolastine, compared with hyoscine butylbromide (HBB) used as a reference anticholinergic drug. 2. Although mizolastine, a potent and selective H1‐receptor blocker has no affinity for muscarinic receptors and does not antagonize the effects of carbachol in rodents, a study was initiated to investigate its effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…18 The separation of peripheral and central effects of antihistamines is of great importance in clinical situation where patients with allergies take their medication while continuing to undertake some of the risk prone activities of everyday living, including car driving, operating machinery and even domestic and recreational behaviour and where impaired judgment and /or skill could lead to accident or injury. 6,10,14 Our study has demonstrated that mizolastine 10 mg and loratadine10mg caused a marked inhibition of histamine induced wheal and flare response in healthy volunteers as compared to placebo, that histamine induced skin prick test response is seen from first assessment at 1 hour after dosage to the last assessment of 24 hours after dosage. In addition, the degree of inhibition seen with mizolastine was comparatively more significant.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…18 The separation of peripheral and central effects of antihistamines is of great importance in clinical situation where patients with allergies take their medication while continuing to undertake some of the risk prone activities of everyday living, including car driving, operating machinery and even domestic and recreational behaviour and where impaired judgment and /or skill could lead to accident or injury. 6,10,14 Our study has demonstrated that mizolastine 10 mg and loratadine10mg caused a marked inhibition of histamine induced wheal and flare response in healthy volunteers as compared to placebo, that histamine induced skin prick test response is seen from first assessment at 1 hour after dosage to the last assessment of 24 hours after dosage. In addition, the degree of inhibition seen with mizolastine was comparatively more significant.…”
Section: Discussionmentioning
confidence: 96%
“…An average of the 2 readings was taken to calculate the salivary flow in gram/minute. 10 The study was conducted in three volunteers per batch with a washout period of one week between each run. On the evening of the previous day of the study .they were housed in the research ward overnight and nothing was allowed orally after 10pm.On the day of the study, they were evaluated in the pharmacodynamic laboratory.…”
Section: Measurement Of Salivary Flowmentioning
confidence: 99%
See 1 more Smart Citation
“… 12 At therapeutic doses, the drug has been shown to be devoid of anticholinergic and sedative effects, and does not significantly disrupt psychomotor performance. 13–15 …”
Section: Introductionmentioning
confidence: 99%
“…It has been found to inhibit histamine-induced weal and flare at doses of 2 mg and above ) and has been found to be clinically effective in allergic rhinitis at a once-daily dose of 10 mg (Stern et al 1992). Mizolastine has also been shown to lack the potent anticholinergic effects of earlier antihistamines: no effects related to muscarinic receptor blockade were found at four times the therapeutic dosage of 10 mg (Danjou et al 1992).…”
mentioning
confidence: 99%